Risk of health status worsening in primary infertile men: A prospective 10‐year follow‐up study. (4th September 2021) - Boeri, Luca; Ventimiglia, Eugenio; Cazzaniga, Walter; Pederzoli, Filippo; Fallara, Giuseppe; Pozzi, Edoardo; Belladelli, Federico; Baudo, Andrea; Frego, Nicola; Capogrosso, Paolo; Alfano, Massimo; Montorsi, Francesco; et al.
Abstract: Background: A severe male infertility factor has been associated with both lower health status and increased mortality in infertile men. Objectives: To investigate reproductive factors associated with health status impairment in infertile men over a 10‐year time frame since the first clinical evaluation. Materials and methods: Data from 899 infertile men were analysed at baseline between 2003 and 2010. Health‐significant comorbidities were scored with the Charlson Comorbidity Index. Patients were followed up yearly recording any worsening in their health status until 2019. Cox regression models were used to estimate hazard ratios and 95% confidence intervals of Charlson Comorbidity Index score increase. Results: At a median follow‐up of 136 months (Interquartile range: 121, 156), 85 men (9.5%) depicted an increase of their baseline Charlson Comorbidity Index score of at least one point. The most frequent reason for Charlson Comorbidity Index upgrade was cancer (34%), cardiovascular diseases (29%) and diabetes mellitus (22%). Compared to patients without a Charlson Comorbidity Index increase, patients with a Charlson Comorbidity Index increase presented with higher body mass index and follicle‐stimulating hormone values, a higher rate of baseline Charlson Comorbidity Index ≥ 1 (all p < 0.01) and a greater proportion of non‐obstructive azoospermia ( p < 0.001). In the Cox regression model, the patient's BMI ( p < 0.001), baseline Charlson Comorbidity Index ≥ 1 ( p < 0.01) and azoospermia status ( p = 0.001) were found to be independently associated with Charlson Comorbidity Index increases. Conclusions: Almost 10% of men presenting for primary infertility had a decrease of the overall health status already in the relatively short 10‐year time frame after the first presentation. Non‐obstructive azoospermic men showed the worst health status impairment and should be strictly followed‐up regardless of their fertility status.